Promoting environmental sustainability through eco-friendly products: A critical review for sustainable development - Michael Ikenna Udodiugwu; Ugochukwu Jude Obikaor; Kingsley Enyinna Eneremadu; Njoku Christian Onwuegbuchulem; Chioma Ezinwanne Anyaegbunam (Annals of Management and Organization Research, 2025)
Purpose: This study was conducted to address critical issues that affect the sustainability of the environment and to recommend eco-friendly policies for driving sustainable economic growth and development. Research Methodology: This study employed a qualitative approach by reviewing the extant literature to assess key concepts and theories, thereby providing comprehensive recommendations for individuals, households, corporate organizations, and governments. Results: The study observed that the implementation of environmental sustainability measures in Nigeria and other developing nations may be delayed due to a lack of readiness, but it is crucial to overcome this. Limitations: This study used a qualitative approach. However, we observed that Nigeria significantly lags in embracing emerging technology, and this study identified areas for improvement and emphasized guidelines to steer purchasing decisions toward sustainable development. Contribution:  This study contributes to knowledge by adding more perspectives to the body of literature and also makes mankind understand that eco-friendly products are indispensable in shaping a sustainable future, promoting health, supporting the circular economy, and contributing significantly to cultivating a more sustainable and environmentally conscious society. Funding: The researchers did not receive any funding from any agencies or institutions; rather, this study was funded specifically through the personal purpose of the researchers.